Topological analysis of carbon and boron nitride nanotubes - Yousaf, Awais (Sci Rep, 2020)
Graph theoretical concepts are broadly used in several fields to examine and model various applications. In computational chemistry, the characteristics of a molecular compound can be assessed with the help of a numerical value, known as a topological index. Topological indices are extensively used to study the molecular mechanics in QSAR and QSPR modeling. In this study, we have developed the closed formulae to estimate ABC, ABC(4), GA, and GA(5) topological indices for the graphical structures of boron nitride and carbon nanotube.